2020
DOI: 10.1093/ajh/hpaa096
|View full text |Cite
|
Sign up to set email alerts
|

Use of RAAS Inhibitors and Risk of Clinical Deterioration in COVID-19: Results From an Italian Cohort of 133 Hypertensives

Abstract: Background The effect of chronic use of renin–angiotensin–aldosterone system (RAAS) inhibitors on the severity of COVID-19 infection is still unclear in patients with hypertension. We aimed to investigate the association between chronic use of angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) and COVID-19 related outcomes in hypertensive patients. Methods A single center study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 16 publications
3
98
1
3
Order By: Relevance
“…For example, in a study by Mehta et al in the United States, showed no signi cant association between ACEI/ARB use and mortality, while it reported potential harmful effects with ACEI/ARB use including higher hospital and ICU admissions [20]. Another study in France by Liabeuf [21]. Interestingly, in another large cohort study from the UK, Black Africans on ACEI/ARB were found to have higher risk of COVID-19 disease [50].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, in a study by Mehta et al in the United States, showed no signi cant association between ACEI/ARB use and mortality, while it reported potential harmful effects with ACEI/ARB use including higher hospital and ICU admissions [20]. Another study in France by Liabeuf [21]. Interestingly, in another large cohort study from the UK, Black Africans on ACEI/ARB were found to have higher risk of COVID-19 disease [50].…”
Section: Discussionmentioning
confidence: 98%
“…Certainly, the contradictory ndings reported in different populations with regards to the severity of COVID-19 may suggest population differences at play [20][21][22][23] [47][48][49]. For example, in a study by Mehta et al in the United States, showed no signi cant association between ACEI/ARB use and mortality, while it reported potential harmful effects with ACEI/ARB use including higher hospital and ICU admissions [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The screening process was shown in figure 1 and 3860 studies were identified according to the research strategy initially. In total, 22 studies containing 12795 patients were adopted in our study and all of them were published in English 10,12,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . Among trails included, half of them were RCTs, and the other were Non-RCTs.…”
Section: Literature Researchmentioning
confidence: 99%
“…Unfortunately, the number of patients who were on ACE-I/ARB therapy was too small (19/187) to reach any conclusion [ 4 ]. Similarly, few other observational studies have failed to demonstrate any association between the use of ACE-I/ARB and increased risk and severity of infection with SARS-CoV-2 [ 17 19 ].…”
Section: Ace-i/arb In Covid-19mentioning
confidence: 99%